An Efficient Synthesis of 2,4,6-Triarylpyridines via Solvent-Free Reaction between Acetophenoneoximes and Aldehydes - Mahernia, Shabnam; Mahdavi, Mohammad; Adib, Mehdi (Synlett, 2014)
An efficient synthesis of 2,4,6-triarylpyridines is described. Heating a mixture of an acetophenoneoxime and an aldehyde under solvent-free conditions afforded Kröhnke pyridines in excellent yields. In this method acetophenoneoximes are directly used for the preparation of Kröhnke pyridines under metal-free conditions.
Keywords: 2,4,6-triarylpyridines; acetophenoneoximes; aldehydes; solvent-free synthesis; cyclizations; heterocycles